Archives in the stacks: documentary editions in collections. (23rd August 2019) - Riter, Robert B.
Abstract : Purpose: This paper aims to investigate the role of documentary editions in supporting the development of historical collections in libraries, their function as evidential and informational objects and considerations for their evaluation in collection development. Framed as objects possessing bibliographic and archival characteristics, attention is given to the evaluative challenges these objects present during collection development. Design/methodology/approach: This paper provides an archival and bibliographic analysis of documentary editions through examining and discussing their archival and bibliographic elements. Consideration is given to how these elements are expressed as information and evidence, how they operate as scholarly and archive-like objects and how they acquire value as collected objects. This approach clarifies the informational and evidential characteristics of these works, offering a framework for their evaluation in libraries. Findings: Documentary editions possess archival and bibliographic characteristics, requiring that evaluators critique the scholarly value and archival integrity of their content. This has implications for the curation of archival objects in library collections, where library and archival expertise can support a more nuanced assessment of these works. Originality/value: The blurred documentary character of these works has been identified by scholars (Cox, 1991). This paper presents evaluative considerations. Here, these characteristics are clarified, and an approach for evaluating these works is offered.